Some Disputable Issues of the Chernigov Land Cities Localization(About the Location of Vorgol, Birin and Zholvazh) - D. I. Chursin (Историко-географический журнал)
Based on the analysis of a wide range of sources, the article justifies location of South Rus’ several cities. Vorgol, known from the chronicled reports of the princes of Posem’ye struggle with the basqaq Akhmat, is related to the Volokitinsky archaeological complex on the Kleven River. It is suggested that this city was transferred from Glukhov princes to Rylsk Principality shortly before the above-mentioned events. It is shown, that mentioned in the “List of Russian cities far and near” Birin and Zholvazh were on the Psyol River: the first one – in the area of the current city of Sumy, and the second — near the village of Gornal. Special attention is paid to methodological issues of historical places localization. It is noted that neglecting toponymical data and unheeding reading of written sources, as well as uncritical perception of the scientific findings of the past centuries, can significantly distort the picture of historical reality, reconstructed by researchers.